Penggunaan Kitosan sebagai Koagulan Alami dalam Perbaikan Kualitas Air Danau - Hendrawati Hendrawati; Susi Sumarni; . Nurhasni (Syarif Hidayatullah State Islamic University, 2015)
Treatment of groundwater and surface water is still dirty often done using synthetic coagulant poly aluminum Cloride (PAC). In fact, its use may pose a risk to health and more expensive. This study was conducted to see the effect of chitosan from shrimp shell waste as a natural coagulant coagulant synthetic substitute. Chitosan at a concentration of 20 ppm lower the lake water turbidity of 94.43%, lowering the pH, decreases the amount of bacteria ± 99.18%. Lower levels of dissolved metals in the water of the lake, such as manganese, magnesium and iron. Chitosan does not change tempeatur lake water and water treatment results. Chitosan not lower BOD value and not lower levels of calcium. DOI :http://dx.doi.org/10.15408/jkv.v0i0.3148